Antibacterial & antitubercular activities of cinnamylideneacetophenones - Polaquini, Carlos R. [UNESP]; Torrezan, Guilherme S. [UNESP]; Santos, Vanessa R. [UNESP]; Nazaré, Ana C. [UNESP]; Campos, Débora L. [UNESP]; Almeida, Laíza A. [UNESP]; Silva, Isabel C. [UNESP]; Ferreira, Henrique [UNESP]; Pavan, Fernando R. [UNESP]; Duque, Cristiane [UNESP]; Regasini, Luis O. [UNESP] (MDPI, 2017)
Cinnamaldehyde is a natural product with broad spectrum of antibacterial activity. In this work, it was used as a template for design and synthesis of a series of 17 cinnamylideneacetophenones. Phenolic compounds 3 and 4 exhibited MIC (minimum inhibitory concentration) and MBC (minimum bactericidal concentration) values of 77.9 to 312 μM against Staphylococcus aureus, Streptococcus mutans, and Streptococcus sanguinis. Compounds 2, 7, 10, and 18 presented potent effects against Mycobacterium tuberculosis (57.2 μM ≤ MIC ≤ 70.9 μM). Hydrophilic effects caused by substituents on ring B increased antibacterial activity against Gram-positive species. Thus, log Po/w were calculated by using high-performance liquid chromatography-photodiode array detection (HPLC-PDA) analyses, and cinnamylideneacetophenones presented values ranging from 2.5 to 4.1. In addition, the effects of 3 and 4 were evaluated on pulmonary cells, indicating their moderate toxicity (46.3 μ M ≤ IC50 ≤ 96.7 μM) when compared with doxorubicin. Bioactive compounds were subjected to in silico prediction of pharmacokinetic properties, and did not violate Lipinski's and Veber's rules, corroborating their potential bioavailability by an oral route.
Keywords: Antibacterial; Antimicrobial; Antitubercular; Cinnamaldehyde; Cinnamylideneacetophenone; Claisen-schmidt reaction; Mycobacterium